Effects of size, ownership and market power on banking sector efficiency and performance in Persian Gulf countries - Kashmari, Ali (2013)
For decades, the Persian Gulf countries (PGC) (Emirates, Saudi, Iran, Qatar, Oman, Kuwait and Bahrain) have been an important financial center among Middle East countries, with the oil industry playing a critical role. The banking sector, thus, has played an important role in influencing the growth of the region for a long time. Recent years have witnessed a growth in the size of the region's banking industry while more than 80% of the PGC banks involve greater assets (more than 1 billion dollars in yearly). In terms of bank ownership, the PGC government owned 47% of the banks in the region, and the size (assets) of PGC banking has increased during recent years. Despite the public ownerships might improve the undeveloped financial systems, the question now is whether government ownership has positive effect on the PGC banking sector. Therefore, this study (i) evaluates the technical efficiency in banking system using data from 103 PGC banks, where the technical efficiency is computed by using the Data Envelopment Analysis (DEA) (ii) investigates the effects of bank size and ownership on efficiency of PGC banks. The efficiency is estimated using panel least square, random and fixed effects, bootstrap and censored truncated Tobit models, and (iii) examines the impacts of market power and efficiency on the performance of PGC banks, using the generalized method of the moments (GMM), white and white-robust tests. The PGC countries include Emirates, Saudi, Iran, Qatar, Oman, Kuwait and Oman, and the sample period is covering from 1996-2010. The empirical results show that the technical efficiency of PGC banks has decreased from 1996 to 2010. With respect to the effects of bank size and ownership on efficiency, the findings indicate that bank size is negatively associated with efficiency, but ownership in terms of private and public ownerships arc positively associated with efficiency. Lastly, the market power has positive and statistically significant determinant of banking performance. The findings also demonstrate that bank size is positively associated with banking performance, where the performance indicator is proxied by banking income. However, the effect of bank size is negative and statistically significant determinant of banking performance where return of assets is employed as a proxy for performance. Banking sectors in this region need to improve their efficiencies by strengthening distribution and using effective allocation of inputs in the financial process. Despite public ownerships being supported by their political influence in banking, governments need to expect the banking sector to perform well. On the other hand, private bank ownerships need to develop regulatory units in the banking system. The important role of PGC government is to ensure the investments in the region are productive and complement with the efficient banking system, which is in line with the greater size of banks. The banks should follow farsighted decisions when they increase the assets in the financial sector, especially when the oil prices increase and when liquidity is high in the country.